2022
DOI: 10.3390/foods11203225
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of a Novel D-allulose 3-Epimerase from Blautia produca and Its Application in D-allulose Production

Abstract: D-allulose is a natural rare sugar with important physiological properties that is used in food, health care items, and even the pharmaceutical industry. In the current study, a novel D-allulose 3-epimerase gene (Bp-DAE) from the probiotic strain Blautia produca was discovered for the production and characterization of an enzyme known as Bp-DAE that can epimerize D-fructose into D-allulose. Bp-DAE was strictly dependent on metals (Mn2+ and Co2+), and the addition of 1 mM of Mn2+ could enhance the half-life of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The K m value of CbDAE for D-fructose was 46.5 mM, lower than 94.5 mM of T. caenicola DAEase from T. caenicola ( Chen et al, 2021 ), 141.3 mM of DaeM from Thermal aquatic habitat ( Patel et al, 2020 ) and 237.5 mM of Bp-DAE from B. produca ( Tang et al, 2022 ), showing stronger affinity for D-fructose. By contrast, the k cat / K m value of CbDAE for D-fructose was 1.10 s −1 mM −1 , which was lower than the 2.2 s −1 mM −1 of DAE from T. caenicola ( Chen et al, 2021 ) and 3.3 mM −1 of DAE from Dorea sp.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The K m value of CbDAE for D-fructose was 46.5 mM, lower than 94.5 mM of T. caenicola DAEase from T. caenicola ( Chen et al, 2021 ), 141.3 mM of DaeM from Thermal aquatic habitat ( Patel et al, 2020 ) and 237.5 mM of Bp-DAE from B. produca ( Tang et al, 2022 ), showing stronger affinity for D-fructose. By contrast, the k cat / K m value of CbDAE for D-fructose was 1.10 s −1 mM −1 , which was lower than the 2.2 s −1 mM −1 of DAE from T. caenicola ( Chen et al, 2021 ) and 3.3 mM −1 of DAE from Dorea sp.…”
Section: Resultsmentioning
confidence: 79%
“…The result above was similar to previously reported DAE family enzymes that specifically favor D-allulose, such as the DAEs from C. cellulolyticum ( Mu et al, 2011a ), Rhodopirellula baltica ( Mao et al, 2020 ) and S. aureus ( Zhu et al, 2019a ), which shared the highest substrate preference against D-alllulose and relatively lower activity against other sugars. In addition, it can be seen that CbDAE displayed higher relative epimerization activity on D-frutcose (68.2%) than that of Bp-DAE (33.4%) from Blautia produca ( Tang et al, 2022 ), Ap-DAE (40%) from A. psychrolactophilus ( Laksmi et al, 2022 ), T. caenicola DAEase (48.7%) from T. caenicola ( Chen et al, 2021 ), but lower than that of DaeM from Thermal aquatic habitat (73.5%) ( Patel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the native-PAGE revealed that this enzyme had a dimeric form ( Figure S2B ). Due to the partial absence of amino acids at the C-terminal region (approximately 22–28 residues) ( Figure 1 ), the monomer form of IfDPEase had the lowest molecular weight compared to other monomer forms of DPEases and ketose 3-epimerases, which were approximately 32–34 kDa [ 1 , 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, the DFEase from R. sphaeroides obtained 17% D-psicose after incubation with D-fructose at 40 °C and pH 9.0 for 3 h [ 16 ]. Moreover, Tang et al (2022) [ 4 ] reported that the conversion of D-fructose into D-psicose of ketose 3-epimerase enzymes ranges from 20% to 33%. Therefore, IfDPEase is a good alternative to the production of D-psicose from D-fructose due to its high yield in short reaction times; this contrasts with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation